A Convenient Method for the Synthesis of Imidazo[1,2-a]pyridines with a New Approach - Balalaie, Saeed; Derakhshan-Panah, Fatemeh; Zolfigol, Mohammad Ali; Rominger, Frank (Synlett, 2018)
A new approach for the efficient synthesis of imidazo[1,2-a]pyridines is described. The synthesis was carried out via the reaction of functionalized 2-aminopyridine that were formed through a three-component reaction and phenacyl bromide derivatives.
Keywords: functionalized imidazo[1,2-a]pyridines; 2-aminopyridines; cyclocondensation reaction